Relationship of red cell distribution width-coefficient of variance with the severity of systolic dysfunction in patients of heart failure with reduced ejection fraction - Ali, Md Bonday; Islam, Mohammad Mamoon; Hossain, Md Iqbal; Rahman, Ataur; Rahman, Zillur; Ullah, Mohammad; Akanda, Md Abdul Kader (BIRDEM Medical Journal, 2023)
Background: Red blood cells distribution width (RDW)-coefficient of variance (RDW-CV) is a measure of red blood cell width variation, reported as part of a standard complete blood count. Although it is usually measured as a routine test, actually its values have been only used in the differential diagnosis of anemia and its high values indicate the presence of anisocytosis. It has been demonstrated that RDW could be considered as an independent additional marker of cardiovascular events in patients with heart failure with reduced ejection fraction. However, the role of RDW in patients with heart failure is less known. This study was designed to evaluate the relationship between RDW-CV and severity of systolic dysfunction in patients with heart failure with reduced ejection fraction (HFrEF). Methods: This cross-sectional study was carried out at the Department of Cardiology, Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh from April 2019 to March 2020. This study included 100 consecutive patients with dyspnea, fatigue and fluid retention suggestive of heart failure. Participating subjects were subjected to a detailed history taking, complete physical examination, New York Heart Association (NYHA) class, 12-lead electrocardiogram (ECG) and routine laboratory investigations including RDW-CV calculate from complete blood count were performed. Left ventricular ejection fraction (LVEF) was measured by echocardiography. Results: The study showed statistically significant negative correlation between RDW-CV and LVEF (r = -0.498, p value<0.001). Conclusion: In the study showed that elevated RDW was associated with decreased ejection fraction assessed by echocardiography in patients of HFrEF. Therefore, increased RDW could be used as an additional marker for identifying severity of left ventricular dysfunction. BIRDEM Med J 2023; 13(3): 124-129